2017
DOI: 10.1101/224329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allosteric effects in catalytic impaired variants of the enzyme cyclophilin A may be explained by changes in nano-microsecond time scale motions

Abstract: Abstract:Robust catalyst design requires clear understanding of the mechanisms by which molecular motions influence catalysis. This work investigates the connection between molecular motions and catalysis for the much debated enzyme Cyclophilin A (CypA) in wild-type (WT) form, and a variant that features a distal serine to threonine (S99T) mutation. Previous biophysical studies have proposed that conformational exchange between a 'major' active and a 'minor' inactive state on millisecond timescales plays a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…However, there is a separation of timescales between the NMR results, which indicate ms dynamics in the "core" region, and the T-jump SAXS results here, which indicate μs dynamics. This discrepancy may reflect coupled processes that are related by a population shuffling mechanism 52 and agree with a broad timescale range of side chain dynamics in CypA uncovered by molecular dynamics experiments 53 . In contrast to the S99T mutant, the NH variant lacks the initial fast signal change (k 1 ) in our T-jump experiments, but clearly retains the slow (k 2 ) signal.…”
Section: Discussionsupporting
confidence: 69%
“…However, there is a separation of timescales between the NMR results, which indicate ms dynamics in the "core" region, and the T-jump SAXS results here, which indicate μs dynamics. This discrepancy may reflect coupled processes that are related by a population shuffling mechanism 52 and agree with a broad timescale range of side chain dynamics in CypA uncovered by molecular dynamics experiments 53 . In contrast to the S99T mutant, the NH variant lacks the initial fast signal change (k 1 ) in our T-jump experiments, but clearly retains the slow (k 2 ) signal.…”
Section: Discussionsupporting
confidence: 69%
“…However, there is a separation of timescales between the NMR results, which indicate ms dynamics in the "core" region, and the T-jump SAXS results here, which indicate µs dynamics. This discrepancy may reflect coupled processes that are related by a population shuffling mechanism (Smith et al, 2015) and agree with a broad timescale range of side chain dynamics in CypA uncovered by molecular dynamics experiments (Wapeesittipan et al, 2018). In contrast to the S99T mutant, the NH variant lacks the initial fast signal change (k1) in our T-jump experiments, but clearly retains the slow (k2) signal.…”
Section: Discussionsupporting
confidence: 78%
“…Differential dynamics of cyclophilin A likely plays a role in stabilizing HIV-1 capsid assembly The first example we describe is human cyclophilin A (CypA), a peptidyl-prolyl enzyme that catalyzes the isomerization of peptide bonds from trans to cis form and participates in various biological process such as protein folding, apoptosis, and signaling (Nigro et al, 2013). Many studies have reported dynamic allostery associated with CypA, which couples the active-site and distal residues, regulating the enzymatic activity (Agarwal, 2005;Rodriguez-Bussey et al, 2018;Wapeesittipan et al, 2019). In addition to the native functions, CypA plays an important role in (de)stabilization of HIV-1 capsid and hence is often recruited by HIV-1 during its life cycle in host cells (Lu et al, 2015;Thali et al, 1994).Although the structure of CypA and HIV-1 capsid (CA) have been available for a long time (Gamble et al, 1996), it was not clear how CypA modulates the CA stability until recently, when the cryoelectron microscopy (cryo-EM) structure of CypA-CA assembly was solved at 8 Å (Liu et al, 2016).…”
Section: Analysis Of Cases With No Observed Structural Changes Revealmentioning
confidence: 99%